Exploring choices in higher education: Female and male first-generation students’ trajectories from study aspiration to study satisfaction in Germany - Reinhold, Sarah; Holzberger, Doris; Kosel, Christian; Seidel, Tina (Frontiers in Education, 2022)
Previous studies have pointed out that first-generation students, continuing-generation students and female and male students differ concerning trajectories into and through higher education regarding study program choices and satisfaction. Studies focused on single time points in students' educational trajectories and mainly emanated from the United States. In order to facilitate a longitudinal comparison of students' study program aspirations and choices, as well as study satisfaction and dropout intentions, we analyzed panel data from the German National Educational Panel Study (NEPS), consisting of 1,694 students. We modeled the influence of gender (female, male) and generational status (first-generation, continuing-generation) with multinomial logit regression models. Results show that students' aspirations and choices did not significantly differ concerning generational status whereas gender differences were confirmed once again. Generational status did not reveal significant differences concerning study satisfaction and dropout intentions, whereas differences concerning gender revealed that female students were significantly more satisfied with their studies than male students. Based on our findings, we point out the importance of early counseling and other support to compensate gender differences in study program aspirations and choices. Further research is needed to explore reasons for our findings showing equal aspirations and choices of first- and continuing-generation students, which are opposed to previous studies' findings.